Pendampingan Strategi Pemasaran Digital untuk Meningkatkan Daya Saing Callalily Artisant - Suyanti, Eka; Suciati, Eka Wulan; Sahna, Ellen Neissella; Fitriani, Elvi; Sukma, Yasinta Nirani (Welfare : Jurnal Pengabdian Masyarakat, 2024)
This service activity aims to increase Callalily Artisant's competitiveness through optimizing digital marketing strategies. With a focus on utilizing digital platforms, this service aims to help Callalily Artistic MSMEs understand and implement effective digital marketing strategies. The methods used in this service include training, workshops, and direct mentoring. Training includes a basic understanding of digital marketing, the use of social media, SEO, and creating interesting content. Workshops are held for direct practice in creating content and managing digital campaigns. Mentoring is provided to help implement the strategies that have been learned. The results of the service activities showed an increase in participants' understanding of digital marketing and their ability to manage digital campaigns. Additionally, there was increased interaction and engagement on Callalily Artisant's social media platforms, which contributed to increased sales and brand awareness. This activity succeeded in having a positive impact on advancing MSMEs through effective digital marketing strategies.